College Students' Career Readiness: As Seen from Self-Efficacy and Internship Experience - Tegowati (CV. Get Press Indonesia, 2026)
Education and internship experience play an important role in preparing young people to face the world of work, because it forms adaptability, self-control, and healthy social relationships. This study aims to examine the influence of self-efficacy on college students' career readiness, and to see whether internship experience plays a role as a moderating variable in this relationship. This study uses a quantitative approach with a moderated regression analysis method, data processing using SPSS 27. The results of the study indicate that self-efficacy have a significant influence on college students' career readiness. Self-efficacy plays an important role in shaping individual confidence to set goals and take proactive steps in career planning. However, the results of the analysis also show that internship experience does not play a role as a moderating variable in the relationship between self-efficacy and career readiness. Thus, career readiness is more influenced by internal psychological factors than external experiences such as internships. These findings provide important implications for higher education institutions in designing career development programs based on improving students' psychological aspects.